Estudio técnico económico y financiero de sistemas de manejo semi intensivo e intensivo en la camaronera Santa Cecilia sitio la Pitahaya del cantón Arenillas período 2012 - Granja Rizzo, Rodrigo Bolívar (2012)
The technical study of economic and financial management systems, semi-intensive and intensive shrimp farming in the Santa Cecilia located in Pitahaya-Arenillas-El Oro, was monitored in two pools of 7.5 has a depth of about 1.20, with a seeding rate of 10 and 16 post-larvae / m in each respectively, over a period of 120 days, considering the first crop as semi-intensive and intensive second.The economic analysis was performed by calculation of operating costs where the semi-intensive farming was $ 24,921.97 and intensive cultivation was $ 31,465.57, while profits in the first treatment was greater than $ 27,788.03 unlike the second treatment that was less with $ 17,094.43, the difference being statistically significant.The benefit-cost ratio in semi-intensive farming was $ 2.12 while the intensive cultivation was higher at $ 1.54.The net present value is positive presented with a value of 42,511 in intensive and semi-intensive farming is exceeded $ 69,105.The internal rate of return acceptable to the project presented with 97% in semi-intensive but reported intensive cultivation by 29%.Costs / ha were $ 3323 and $ 4195 respectively in each methodology.The cost / pound of shrimp per treatment applied were $ 2.10 and $ 1.85, it should be noted that the cost / pound depends on size of harvest, crop density and feed conversion. In technical analysis are reported: weight gain of shrimp in semi-intensive farming took 1.5 grams weekly intensive culture unlike that obtained 1.3 grams, reaching a weight of 23.8 grams and 20.4 respectively, at 17 weeks with a feed conversion factor of 1.3 and 1.6, a survival of 80% and 65%, harvesting per hectare amounting to 3345 and 3500lbs in each treatment.